Omni-Channel retailing enhancing unified experience amidst pandemic: An emerging market perspective - Joshi, Sudhanshu; Sharma, Manu; Chatterjee, Prasenjit (Decision Making: Applications in Management and Engineering, 2023)
The research aims to explore the strength of enablers, and adoption barriers present in omnichannel retailing (OCR), and discuss how organizations may focus to redesign their business models in emerging markets to manage the disruptive environment. The prominent enablers may enhance the omnichannel’ performance to deliver a unified experience across all channels during the pandemic time. The paper has used hybrid Multi-Criteria Decision-Making (MCDM) Methods. These methods are widely used by organizations for the exploration of the interrelationship among barriers and enablers affecting their performance. In the current study, 18 experts from different domains have examined and evaluated the 10 barriers and 7 enablers. The study reveals that integration, visibility, internet accessibility, and advanced distribution centers are the prominent enablers and driving the customer analytics enabler to strengthen their customer engagement and providing a unified experience to the. During the pandemic time the usage of the online channels have increased and thus retail channels may consider these enablers to enhance the unified experience level of the customers. The study also shows that inconsistency in price is the main adoption barrier followed by inconsistency in product discounts that should be minimized to engage customers effectively. The retail organizations need to understand the roadblocks in the adoption of OCR and should take relevant actions to minimize them. The retail organization or marketers may redesign their existing strategies based on price consistency, integration, visibility, information systems, and coordination to develop a unified experience across channels during the pandemic situation.